Internet usage time and trust in doctors: evidence from China - Qiuming Gao; Xuechun Wang; Zhen Lin; Zangyi Liao (BMC Public Health)
Abstract Background The growth of internet use has greatly impacted many societal sectors, including healthcare. However, current evidence about the relationship between internet usage time and public trust on doctors is insufficient. Objective To examine the relationship between the time spent on the internet and the level of trust in doctors, and explore its mechanism. Methods Multiple regression models are employed, utilizing a sample of 19,193 observations from the China Family Panel Studies (CFPS) in 2020. First, we regress the relative trust in doctors compared to trust in strangers on internet usage time. Subsample results across distinct population groups are explored. Second, we examine the mechanism of using the internet as an information channel through the mediation method, and further investigate the role of the internet as a communication platform by analyzing the moderation effects of socializing activity as well as social media engagement. Results We find a significant negative relationship between increased internet usage time and trust in doctors. This correlation remains robust across different model specifications and variable measurements. The negative correlation is more pronounced among population groups who are elderly, male, married, with low educational levels, insured and residing in urban areas. The role of the internet as a source of information is validated as a mechanism producing the negative influence. The role of the internet as a communication platform tends to mitigate the negative consequences of internet usage, as engaging in online socializing activity can have a positive moderation effect. However, for social media engagement, its overall effect on trust in doctors is negative, potentially due to social media’s dual function as a communication platform and an information source. Conclusions Although individual-focused literature tends to demonstrate a positive impact of the internet on trust in doctors in China, our study, which focuses on the general public, reveals contrasting results. Our findings imply that the primary manner in which internet usage, encompassing social media usage, influences public trust in doctors is by molding a collective perception of them. Consequently, the medical community may need to take a more proactive approach in expanding online communication channels for interacting with patients and the wider public.